Study On The Effect Of Use Of Luxury Brand During The Social Identity Projection Of Individuals - Butgel Tunalı, Selen (The Turkish Online Journal of Design Art and Communication, 2016)
The “Social Identity Theory”, which has been developed by Henri Tajfel & John Turner, is defined as “the part of personality perception of individual, which is created with an individual’s membership a group, knowledge with this membership, paid attention and emotional commitment on this membership”. Social identity theory, beyond private and personal identities, touches upon the identity of a specific group membership. According to the researches about this issue, individuals reflect their social identities in the society with the products that they consumed and with the brands that they used. In this study, social identity and social identity theory is evaluated by defining the concept of identity firstly. After that, the definition of brand and the brand identity with the definition of luxury and luxury brand is made; in the end, the effect of use of luxury brand during the social identity projection of individuals is touched upon.
Keywords: Brand; Social Identity; Luxury Brand; Marka; Sosyal Kimlik; Lüks Marka